(untitled) (Research, Society and Development, 2022)
Endometriosis is a gynecological disorder characterized by the presence of endometrial tissue outside the uterine cavity related to genetic predisposition, estrogen dependence, progesterone resistance, and inflammation. The retrograde menstruation theory, formulated by Sampson, is the most scientifically acceptable etiology due to similar mechanisms occurring in healthy women. However, several other theories have been raised with different pathophysiological focuses. The pathogenesis of the disease contributes to an immune imbalance, culminating in increased expression of inflammatory and angiogenic mediators and changes in several metabolic pathways. Resveratrol is a polyphenol that has been widely studied for its benefits in controlling inflammatory mediators. In this review, we summarized the most recent findings linking the effects of resveratrol and possible improvements in disease symptomatology. Experimental and in vitro studies have shown beneficial results when evaluated in endometriotic models. However, the same results were not obtained in humans, especially when assessing pain thresholds before and after resveratrol supplementation. In conclusion, the results for clinical practice are still inconclusive.